The Influence of K-pop Brand Ambassador BTS and Brand Image on McDonald’s Purchasing Decisions: Fear of Missing Out (FOMO) as a Mediating Role - Sherlyn Valencia Arief; ⁠Liestyaningrum Rahmadhani Wisnu Putri (Transpublika Publisher, 2025)
McDonald's leveraged popular culture trends through collaboration with BTS (K-Pop idol group) by launching the BTS Meal, successfully capturing the attention of global consumers including those in Indonesia. This phenomenon demonstrates the role of brand ambassadors, brand image, and psychological factors such as Fear of Missing Out (FOMO) in influencing consumer purchasing decisions. The objective of this research is to examine how BTS, acting as a brand representative and shaping the brand's image, impacts the choices customers make when purchasing McDonald’s items. Fear of Missing Out (FOMO) will be considered as a mediating factor. The study is prompted by the partnership between McDonald’s and the popular South Korean group BTS, which caused excitement among consumers worldwide, including in Indonesia. The research method used is a quantitative approach, conducted through a survey of 246 respondents who are McDonald’s customers and BTS fans. The results suggest that having BTS as a brand ambassador positively affects the fear of missing out (FOMO) and buying choices. Furthermore, the brand's image is also shown to have a positive influence on FOMO. The study also reveals that FOMO plays a crucial part in connecting BTS as a brand ambassador, brand image, and purchase decisions. This study implies that strategic collaborations with global celebrities can enhance brand appeal and drive purchasing decisions through psychological mechanisms such as Fear of Missing Out (FOMO). Therefore, companies should take into account the emotional aspects of consumers when designing marketing strategies.